1999
DOI: 10.1039/a807657j
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two adsorbents for diffusive sampling and thermal desorption-gas chromatographic analysis of monoterpenes in air

Abstract: Tube type samplers with two different adsorbents, Chromosorb 106 and Tenax TA, were evaluated by laboratory experiments and field tests for simultaneous diffusive sampling of alpha-pinene, beta-pinene and delta 3-carene and subsequent thermal desorption-gas chromatographic analysis. No statistically significant effects of exposure time, concentrations of monoterpenes or relative humidity were found for samplers with Chromosorb 106 when running a factorial design, with the exception of the adsorption of delta 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 12 publications
0
22
1
Order By: Relevance
“…The present results showed that Tenax TA was a suitable sorbent for TD-GC-MS analysis of monoterpene hydrocarbons, and thus corroborated previous studies [52][53][54]. In contrast with the findings of Coeur et al [55], the present results revealed neither a time nor a temperature effect on the storage of the investigated molecules.…”
Section: Stability Of the Sampling Devicecontrasting
confidence: 53%
“…The present results showed that Tenax TA was a suitable sorbent for TD-GC-MS analysis of monoterpene hydrocarbons, and thus corroborated previous studies [52][53][54]. In contrast with the findings of Coeur et al [55], the present results revealed neither a time nor a temperature effect on the storage of the investigated molecules.…”
Section: Stability Of the Sampling Devicecontrasting
confidence: 53%
“…In addition, the sample storage time was low (1-2 days) with demonstrated stability of monoterpenes on Tenax-TA over this time frame [Sunesson et al, 1999]. While ozone was not removed from the ambient air samples, low volumes of ambient air were collected (1.0 L) and its atmospheric mixing ratios were < 10 ppb on the majority of measurement days.…”
Section: Discussionmentioning
confidence: 99%
“…Carbopack X was used for sampling and analysis of 1,3-butadiene and benzene (Strandberg et al, 2005;Sunesson et al, 2006). The tubes were thermally desorbed in an ATD 400 (Perkin Elmer) connected to a gas chromatography-mass spectrometry (GC-MS) system (Hewlett Packard/Agilent 5973/6890, Stockholm, Sweden).…”
Section: Voc Samplesmentioning
confidence: 99%